(untitled) (Clinics, 2014)
OBJECTIVES: Our previous study demonstrated that superoxide dismutase levels were higher in tuberculous pleural effusions than in malignant pleural effusions, but that this difference could not be used to discriminate between the two. The objective of the present study was to investigate the levels of superoxide dismutase 2 in pleural effusions and to evaluate the diagnostic significance of pleural effusion superoxide dismutase 2. METHODS: Superoxide dismutase 2 concentrations were determined in pleural effusions from 54 patients with tuberculous pleural effusion and 33 with malignant pleural effusion using an enzyme-linked immunosorbent assay (ELISA) kit. Pleural effusion interferon gamma and tumor necrosis factor alpha levels were also analyzed by ELISA. The Mann-Whitney U test was used to evaluate the significance of differences. Associations between superoxide dismutase 2 concentrations and sex, age and smoking habits were assessed using Spearman's or Pearson's correlation coefficient analysis. Receiver operator characteristic analysis was performed to evaluate the value of superoxide dismutase 2 levels in the discrimination of tuberculous pleural effusion from malignant pleural effusion. RESULTS: Superoxide dismutase 2 levels were significantly higher in patients with tuberculous pleural effusion compared with those with malignant pleural effusion (p